Buddhist studies from India to America: essays in honor of Charles S. Prebish - Keown, Damien; Prebish, Charles S. (Routledge critical studies in Buddhism, 2006)
part one: Vinaya studies and ethics -- part two: Buddhist traditions -- part three: Western Buddhism -- part four: Inter-religious dialogue.